SANKSI HUKUM TERHADAP WAJIB PAJAK YANG TIDAK MEMENUHI PANGGILAN DARI PENYIDIK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2007 TENTANG PEMERIKSAAN PAJAK - B, Lusiana Arifin (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTDirektorat Jenderal Pajak should to support an effort for control and founding to taxpayers that can be realized with a tax intensification and ekstensification through tax inspection. And this is a tax inspection role as a control and founding for taxpayers to obey the tax regulation.This research aims to know the role and responsibility of taxpayers and tax instruments about tax inspection, punishment to taxpayers which ignore to tax inspection especially in Samarinda city. The method of this research used yuridis normative and yuridis empiris.The result showed, the taxpayers to obey the regulation with tax inspection is too low. Tax inspection is can’t avoid and should to do because it’s the tax law instrument for test the obey of taxpayers to fill their obligation. The rule about inspection and punishment is regulated on Undang-Undang Nomor 28 Tahun 2007 about The Rule of Tax.